á¹¢uâÅ«bÄt al-Tarjamah min al-NÄá¸¥iyah al-DalÄliyyah - Ismail, Achmad Satori (Al-Jamiah: Journal of Islamic Studies, 2003)
The main problem in the proses of language transfer is to find the precise word between two languages. To transfer a word of a language into another language require some conditions, i.e., word classification, socio-cultural background, metaphor, etc. It is mistaken to say that the meaning of words in any language lies in the pattern of the word used t0 express particular purpose. Instead, the meaning of a word we used as a mean to construct our knowledge is the meaning that suit to the culture of a country. Therefore, the concept of a word in a culture may not be able to be found in other cultures. It is also the cases of Indonesian language in relation to other languages. In particular, the difficulties of translating Arabic words into bahasa Indonesia or vice versa, from the semantic point of view, could be classified into some categories: (1) the semantic difference of two similar words, (2) the differences in using an expression, (3) the classification differences of words, (4) the differences in using taboo words and the softness of expression, and finally (5) the socio-cultural differences between two nations/ countries.